Central Nervous System Pathology Caused by Autoreactive CD8(+) T-Cell Clones following Virus Infection - Tsunoda, Ikuo (American Society for Microbiology, 2005)
Theiler's murine encephalomyelitis virus (TMEV) causes a demyelinating disease in infected mice which has similarities to multiple sclerosis. Spleen cells from TMEV-infected SJL/J mice stimulated with antigen-presenting cells infected with TMEV resulted in a population of autoreactive CD8(+) cytotoxic T cells that kill uninfected syngeneic cells. We established CD8(+) T cell clones that could kill both TMEV-infected and uninfected syngeneic targets, although infected target cells were killed more efficiently. The CD8(+) T-cell clones produced gamma interferon when incubated with either infected or uninfected syngeneic target cells. Intracerebral injection of the clones into naïve mice induced degeneration, not only in the brain, but also in the spinal cord. This suggests that CD8(+) Tc1 cells could play a pathogenic role in central nervous system inflammation.